THE CURRENT SITUATION OF HUMAN RESOURCE AND SOME INFLUENCING FACTORS AT SONG CAU DISTRICT HEALTH CENTER IN 2017-2019 (Vietnam Journal of Community Medicine, 2020)
The cross-sectional description research, combining quantitative and qualitative aims to fulfill two objectives: (1) To describe the current situation of human resource and (2) To analyze factors affecting the current situation of human resource at Song Cau District Health Center in 2017-2019. The research results show that the quantity of preventive healthcare personnel complies with the current regulations, and the workfore has an appropriate age (53.9% is 30 - 50 years old). Regarding structure of expertise, it is still inappropriate with low proportion of doctor (10.4%). In term of educational level, the proportion of undergraduate health worker (including doctor) at the Health Center (71.4%) is higher than the overall national proportion, while this proportion at Health Station is lower (8.8%). Some of the factors positively influence the current situation of human resource including: benefit policies under Resolution 110/2014/NQ-HDND; improved human resource planning and recruitment process; the infrastructure system; improved employee evaluation process; encouragement for training. Besides, some negative influencing factors include: unclear employee evaluation; lack of funding to support training; low income.
Keywords: Human resource, health workers, preventive medicine